ANALISIS HUKUM MENGENAI SURAT KETERANGAN ASAL (SKA) UNTUK BARANG EKSPOR INDONESIA - Muhammad Dian Ansyari (Badamai Law Journal, 2016)
The purpose of this thesis is to study the rules and legislations related with the implementation of Certificate of Origin (COO) preference as a supporting document which must be complied in export trade and to study the rules and legislations towards the solution to the problems on Certificate of Origin (COO) preference as a document indicating the origin of particular goods. The method of this research is normative legal research by collecting statutory regulations on Certificate of Origin (COO), identifying the problems, and analyzing them qualitatively. The results of this thesis research show that: firstly, with regard to the implementation of Certificate of Origin (COO) preference as a supporting document which must be complied in export trade, it is a fact that there is lack of principle of prudence in the material content of the regulations on Certificate of Origin (COO) of Indonesian export goods. This condition has caused that it is easy to abuse, devert, and falsify the document of Certificate of Origin (COO). More over, the control of the issuing institution of the Certificate of Origin (COO) is very weak and the coordination among the governmental ministries is not well cohesive. The management system of office administration in charge which is not well organized has worsened and added bad cases related with the documents of Certificate of Origin (COO) of Indonesian goods in the export destination countries.